Manajemen Konflik Perkawinan dalam Perspektif Al-Qur’an: Marital Conflict Management in the Perspective of Al-Qur'an - Saadi, Anwar (Direktorat Jenderal Bimbingan Masyarakat Islam, 2024)
Disputes and conflicts between spouses are common occurrences within a family. However, if not properly addressed, they can jeopardize family harmony and even lead to divorce. This study aims to explore the Qur'anic approach to resolving family conflicts. Through an analysis of Qur'anic verses, particularly QS.4, Annisa:34-35, this research highlights the concept of islah (reconciliation) as a comprehensive solution. Islah emphasizes a gradual resolution, starting from advice to mediation by a third party. Findings indicate that the Qur'anic approach provides a strong foundation for addressing family conflicts while maintaining the values and goals of marriage. The practical implication of this research underscores the importance of applying the islah approach in managing family conflicts to prevent divorce and preserve marital harmony. By understanding and implementing the principles contained in the Qur'an, married couples can confront differences constructively, strengthen their relationship, and prevent the escalation of conflicts that could damage the family. The findings of this research contribute to strengthening family values based on religious principles and provide guidance for family counseling practitioners and stakeholders involved in addressing marital conflicts.